Ensino de leitura nas séries iniciais do ensino fundamental: uma proposta teórico-metodológica com o livro-imagem onda (Suzy Lee) - Barbosa, Jakecilene Lindolfo (2023)
In basic education, more specifically in the last two years of the initial grades of elementary school, levels in which students should have already consolidated the literacy process, the difficulties in reading are evident. We find in the classrooms children who decode texts, but are unable to go beyond the linguistic materiality to produce meaning. In this context, we chose to distance ourselves from reading comprehension as a word decoding skill, understanding it in this research as an activity of meanings production which integrates author-text-reader and considers the relations between the enunciator's persuasive actions (author) and the enunciatee’s interpretative actions (reader). This paper purposes to discuss how to teach reading in the early grades of elementary school based on a picture-book. Considering this guiding problem, we aim to develop a theoretical and methodological proposal with the picture-book Wave (Suzy Lee) for teaching reading in the early grades of elementary school in the light of discursive semiotics. As a fundamental theoretical reference, we chose discursive semiotics for our analyses, in addition to relying on other authors who helped us in the reflection on the conceptions and reading strategies, as well as in the understanding of the specificities and potentialities of the picture-book. Aiming to achieve this goal, we formulated the following steps: a) Reflect on the teaching of reading, dialoguing with our own experience; b) Systematize knowledge about discursive semiotics and the plastic categories that constitute the visual text; c) Analyze the book Wave (Suzy Lee) from the Meaning Generative Path; d) Plan strategies and teaching activities for reading the book Wave (Suzy Lee) based on Solé (1998). The study is qualitative in nature and was organized according to the following theoretical and methodological path: 1. Bibliographic research from already published materials – books, articles, dissertations and theses; 2. Semiotic analysis of an object – the picture-book Wave (Suzy Lee); 3. Pedagogical approaches for the reading of the analyzed object. The analysis revealed that Wave (Suzy Lee) addresses the isotopy of childhood as the passage from the state of not knowing to the state of knowing figuratively represented by the experience of discovering the sea by a little girl. In the text, the artist mobilizes plastic formants, figurative formants and the graphic design itself, exploring the diferente parts that composse the object book (cover, back cover, endpaper, fold) to create the meaning of the narrative. We intend that the reading proposal elaborated, in pedagogical script format, with the picture-book Wave (Suzy Lee) may help the work of Portuguese Language teachers who teach in the initial grades of elementary school, configuring itself as one more possibility to expand the reading practices in the public "school ground".